Argumentation as a Strategy for Conceptual Learning of Dynamics - BEKİROĞLU, FERAL (SPRINGER, 2013)
Researchers have emphasized the importance of promoting argumentation in science classrooms for various reasons. However, the study of argumentation is still a young field and more research needs to be carried out on the tools and pedagogical strategies that can assist teachers and students in both the construction and evaluation of scientific arguments. Thus, the aim of this study was to evaluate the impact of argumentation on students' conceptual learning in dynamics. True-experimental design using quantitative research methods was carried out for the study. The participants of the study were tenth graders studying in two classes in an urban all-girls school. There were 26 female students in each class. Five argumentations promoted in the different contexts were embedded through the dynamics unit over a 10-week duration. The study concludes that engaging in the argumentative process that involves making claims, using data to support these claims, warranting the claims with scientific evidence, and using backings, rebuttals, and qualifiers to further support the reasoning, reinforces students' understanding of science, and promotes conceptual change. The results suggest that argumentation should be employed during instruction as a way to enable conceptual learning.
Keywords: Argumentation; Conceptual learning; Physics education; High school students; STUDENTS ARGUMENTATION; SCIENCE-EDUCATION; DECISION-MAKING; KNOWLEDGE; THINKING; ENVIRONMENTS; PEER